The effects of depersonalization and organizational cynicism levels on the job satisfaction of educational inspectors - Arabaci, I. Bakir (Academic Journals, 2010)
This study aimed to establish whether depersonalization and organizational cynicism levels of educational inspectors affected their job satisfaction with respect to certain demographic variables. Data were collected from 217 participants by using the Maslach Burnout Inventory's Depersonalization dimension, Brandes' Organizational Cynicism Scale and Minnesota Satisfaction Questionnaire. The results revealed that educational inspectors experienced low depersonalization, moderate organizational cynicism, and were undecided about their job satisfaction levels. While the variables of gender, marital status, title and the city of assignment did not account for a meaningful difference in depersonalization, organizational cynicism and job satisfaction levels, the variables of age, seniority and the region of assignment did. In addition, a negative relationship existed between educational inspectors' job satisfaction and their depersonalization and organizational cynicism levels. Depersonalization and organizational cynicism predicted job satisfaction meaningfully.
Keywords: Depersonalization; organizational cynicism; job satisfaction; educational inspectors